A proposed model for activating and rationalizing the process of recruiting human competencies - a field study in some Algerian universities - Arioua , Nesma; Benyamina, Said (Journal of Social Sciences and Humanities, 2023)
In general, members of the faculty cannot be separated from the university or society. This is due to the functions and roles played by this category, contributing to the teaching, formation, framing, and preparation of students for developing and serving the community, as well as contributing to the development of scientific research and supervision of laboratories in order to ensure the quality of higher education on the one hand. It also has very effective roles in the management of the university on the other hand... All are interconnected roles that aim to achieve quality in higher education, provided that the member of the faculty must be appointed based on merit under the principle of “placing the right person in the right place”. This study, therefore, aims a serious attempt to reach a set of proposals aimed at the so-called quality of employment under the rationale of selecting human resources with outstanding competencies in education, research, and community service. In order to reach the study’s objectives, the two researchers relied on the descriptive approach, the questionnaire form as a major data collection tool, and the SPSS program for analysis. 108 individuals (40%) were selected from the total community of 271 individuals. Through the statistical analysis, the results of the study showed that: there had been a change in the criteria for the recruitment of faculty members by changing the university education system from Classic to LMD, we find a clear positive orientation from the study sample toward selection and appointment criteria despite the existence of shortcomings that culminated in the study’s proposals, and the recruitment interview must be reconsidered due to the bias and subjectivity that the latter opens.